Unlocking the antibacterial potential of xanthone from calophyllum species: inhibition of nucleic acid synthesis - Abang Heilman, Dayang Nurul Anisa; Hui, Audrey Yong Chee; Mian, Vivien Jong Yi; Ahmad, Fasihuddin Badruddin (Wiley, 2023)
Plants are valuable resources for the development of novel pharmaceutical products. The increasing threat to global health caused by antibiotic resistance remains a serious concern, driven a need to discover and evaluate novel anti‐bacterial agents. Calophyllum species are known for having excellent biological activity due to its secondary metabolites, such as xanthone. Numerous xanthones have been found to possess anti‐bacterial properties that are effective against plant pathogens, hence can be applied to fight human pathogens. Topoisomerase enzymes (DNA gyrase and topoisomerase IV) are DNA metabolism enzymes that possess distinct roles as unlinking enzymes during DNA replication. Nucleic acid synthesis inhibition reduces bacteria proliferation through the inhibition of topoisomerase enzymes that are essential for bacterial growth. The xanthone isolated from Calophyllum and its anti‐bacterial were discussed in this review. Besides, molecular docking simulations were applied to explore the potential binding mode of xanthones to DNA metabolism enzymes. The docking study displayed that biscaloxanthone is a good topoisomerase enzymes inhibitor compared to their co‐cystalize ligand, novobiocin and BDBM50198240. The complied information and molecular docking simulations suggested that xanthone isolated possesses potential anti‐bacterial agents inhibiting nucleic acid synthesis. Besides, it suggested that the anti‐microbial activity of xanthone contributes from the topoisomerase enzyme‘s inhibition.